Prevalence and Pattern of Peptic Ulcer Disease among Patients Undergoing Upper Gastrointestinal Endoscopy in Koshi Hospital: A Cross-Sectional Descriptive Study - Thakur, Manoj Kumar; Yadav, Rohit Kumar; Yadav, Rajeshwar; Sharma, Priyanka (Journal of Nobel Medical College, 2024)
Background: Acid peptic disease is one of the most common diseases encountered in outpatient department. There has been limited study on prevalence of different types of peptic diseases among patients undergoing upper gastrointestinal endoscopy especially in eastern part of Nepal. The aim of this study was to find out prevalence of different types of peptic diseases and study the socio-demographic profile of patients attending our medicine department.Materials and Methods: A cross-sectional descriptive study conducted from April 2024toSeptemer 2024 who presented with symptoms of dyspepsia and features of upper gastrointestinal bleeding in medicine department were included. Data were collected from patient charts, endoscopy reports and pathology report. Statistical analysis was done using statistical package for the social sciences (SPSS) software version 17.Results:  A total of 569 patients were evaluated, among them 281 were males (49.4%) and 288 (50.6%) were females. Gastritis both nonerosive 219 (38.5%) and erosive 136 (23.9%) were common endoscopic findings. It was followed by gastric ulcer 65 (11.4%) and duodenal ulcer 27(4.7%). Normal endoscopic finding was present in 63 (11.07%). The prevalence of different types of peptic diseases was 88.9 percent among patients undergoing endoscopy. The peak incidence of peptic ulcer disease was present in age groups 40-60. Gastric ulcer and duodenal ulcer were significantly higher in male whereas non erosive gastritis was significantly higher in female.Conclusion: Acid peptic disease is very common in patients undergoing endoscopy in our center. Gastric ulcer and duodenal ulcer were significantly higher in males whereas non erosive gastritis was significantly higher in females. Racial variation in peptic ulcer disease was not statistically significant.